A standard view of the role of the marketing audit entrance in improving the performance of marketing mix decisions - sahi, Mostapha (Journal of Excellence for Economics and Management Research, 2022)
There are usually indirect relationships with some levels and fields of knowledge, Among the regular elements of the components of trade and economics are the overlap between administrative functions. So that these alignments do not appear between functions and how they interact… Among them is accounting and marketing, Hence the question turns into a problem About specific particles in between Marketing audit and the performance of marketing mix decisions. For this reason it has been studied Input In rationalizing these decisions And turn them into results Marketing audit is an effective tool in functional measurement For marketing, By analyzing the performance of the marketing mix (product, price, promotion, communication) And his role in improving the marketing policy And thus issuing decisions